2014
DOI: 10.1371/journal.pone.0103793
|View full text |Cite
|
Sign up to set email alerts
|

AdipoR1/APPL1 Potentiates the Protective Effects of Globular Adiponectin on Angiotensin II-Induced Cardiac Hypertrophy and Fibrosis in Neonatal Rat Atrial Myocytes and Fibroblasts

Abstract: Atrial hypertrophy and fibrosis are essential pathological features of atrial fibrillation. Recently, adiponectin has become a protein of interest due to its beneficial effects on cardiovascular diseases. However, the molecular mechanism of atrial structural remodeling and signaling pathways evoked by adiponectin remain unclear. In the present study, we investigated the cardioprotective effect of globular adiponectin (gAcrp) on angiotensin II-induced atrial hypertrophy and fibrosis in neonatal Sprague-Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Many studies have documented the involvement of ADPN in the termination of inflammation by at least two mechanisms: the first is through the inhibition of the function of mature macrophages and the second is the growth of granulocyte-monocyte progenitor cell lines. The former mechanism plays an important role in acute inflammation while the latter mechanism plays a major role in chronic inflammation in order to avoid excessive immune response (Antonopoulos et al, 2014;Cao et al, 2014;Li et al, 2015). Additionally, the findings in our present study demonstrate that the serum level of ADPN in mice increase in the early period of HS, which is in accordance with the varying trend of IL-37 in the same HS model.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have documented the involvement of ADPN in the termination of inflammation by at least two mechanisms: the first is through the inhibition of the function of mature macrophages and the second is the growth of granulocyte-monocyte progenitor cell lines. The former mechanism plays an important role in acute inflammation while the latter mechanism plays a major role in chronic inflammation in order to avoid excessive immune response (Antonopoulos et al, 2014;Cao et al, 2014;Li et al, 2015). Additionally, the findings in our present study demonstrate that the serum level of ADPN in mice increase in the early period of HS, which is in accordance with the varying trend of IL-37 in the same HS model.…”
Section: Discussionsupporting
confidence: 87%
“…Adiponectin protects against cardiac dysfunction induced by MI or angiotensin II via suppressing cardiac hypertrophy and interstitial fibrosis [3,11,32]. Globular adiponectin attenuates myocardial ischemia/reperfusion injury [13].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported exaggerated pathological cardiac hypertrophy in adiponectin knockout mice under experiment models of pressure overload (61-63) with adiponectin replenishment resulting in reduced pathologic hypertrophy (62). Experiments in isolated neonatal rat ventricular myocytes treated with angiotensin II to induce hypertrophy illustrated that the primary anti-hypertrophic mechanism of adiponectin occurred through AdipoR1-APPL1-AMPK activation resulting in suppression of nuclear factor kappa-B-induced hypertrophic growth signaling (64)(65)(66). These studies suggest that adiponectin can protect against cardiac hypertrophy and lack of adiponectin can lead to development of more severe pathological hypertrophy.…”
Section: Physiological Effects Of Adiponectin and Implications In Carmentioning
confidence: 99%